China's Belt and Road Initiative in the East African Community : shaping a China-Centric regional order - Mboya, Cliff (2023)
Zusammenfassung: China is reorganising the spatial order in the East African Community through influencing key stakeholders. By heavily investing in regional connectivity projects via the BRI, Beijing promotes an alternative idea of development - one that is favourable to a Chinese-centric order in the region